Integrasi Literasi Keuangan dalam Kurikulum Pendidikan Ekonomi di Institut Pendidikan Tapanuli Selatan - Samakmur, Samakmur; Rambey, Mara Judan; Vebrina, Dinda (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to evaluate the level of financial literacy integration within the Economic Education curriculum and to identify dominant and underdeveloped dimensions of financial literacy among students. The research was conducted at the Economic Education Study Program of the Institute of Education Tapanuli Selatan, involving 146 active students as respondents. The research method employed a descriptive quantitative approach, using a Likert-scale questionnaire developed based on financial literacy indicators from Atkinson & Messy (2012) and Lusardi & Mitchell (2014). The findings reveal that the integration of financial literacy into the curriculum is categorized as high, with an average score of 75.49%. The highest score was obtained in the area of personal financial planning and management (81.18%), while the lowest score was in future financial planning (68.46%). These results indicate that short-term financial literacy is well addressed in the learning process, whereas long-term financial planning requires further emphasis. This research concludes that although financial literacy integration is present, the curriculum still needs adjustments to become more practical and contextual. Recommendations include developing specialized financial literacy courses, adopting project-based learning methods, and conducting regular curriculum evaluations to enhance students’ preparedness in facing the challenges of the digital economy